2010
DOI: 10.1111/j.1420-9101.2009.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

The mismeasurement of sexual selection

Abstract: Sexual selection can explain major micro‐ and macro‐evolutionary patterns. Much of current theory predicts that the strength of sexual selection (i) is driven by the relative abundance of males and females prepared to mate (i.e. the operational sex ratio, OSR) and (ii) can be generally estimated by calculating intra‐sexual variation in mating success (e.g. the opportunity for sexual selection, Is). Here, we demonstrate the problematic nature of these predictions. The OSR and Is only accurately predict sexual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
312
3
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(339 citation statements)
references
References 85 publications
(280 reference statements)
18
312
3
6
Order By: Relevance
“…First, high values of I s will have no significance for selection if variance in mating success is random [19]. Second, there is an inherent systematic positive biasing of I s with high ASR [25]. That said, the pattern reported here, showing a negative relation between the sex ratio of the mating pool and the maximum potential for sexual selection, is all the more remarkable.…”
Section: Box 2 the Sex Ratio And Opportunity For Sexual Selection Acmentioning
confidence: 58%
See 2 more Smart Citations
“…First, high values of I s will have no significance for selection if variance in mating success is random [19]. Second, there is an inherent systematic positive biasing of I s with high ASR [25]. That said, the pattern reported here, showing a negative relation between the sex ratio of the mating pool and the maximum potential for sexual selection, is all the more remarkable.…”
Section: Box 2 the Sex Ratio And Opportunity For Sexual Selection Acmentioning
confidence: 58%
“…In so far as mating and parental effort are not entirely compatible, which typically they are not, this suggests that, in populations with a male-biased ASR, we should generally see less male-male mate competition and more monogamy [23]. Indeed, further models focusing specifically on competition show that, contrary to the intuitions drawn from Emlen and Oring [6], a male-biased OSR only accurately predicts intense sexual selection among males under a limited set of circumstances, most specifically where it is possible for one male to monopolize multiple mates (e.g., temporal 'clumping' of females arriving on a lek; [24]) and even then mate monopolization generally becomes more difficult when there are more competitors [25].…”
Section: Glossarymentioning
confidence: 80%
See 1 more Smart Citation
“…Bateman's [2] conclusions have been criticized on experimental and technical grounds [38], or on the grounds that the difference in variance in reproductive success between the sexes can be attributed to purely random processes [39,40], or for other reasons does not reflect the intensity of sexual selection [41,42]. In re-analyses of Bateman's data, both Arnold & Duvall [43] and Snyder & Gowaty [38] concluded that in his experiments, female reproductive success also increases with number of mates (a finding that is now proving commonplace, see [31]), and that number of mates also explains a significant amount of variation in female reproductive success.…”
Section: Bateman's Principlesmentioning
confidence: 99%
“…Variance in male fitness has thus been proposed as a useful measure of the 'opportunity for sexual selection' on males [50,51], commonly now termed I mates , see also [37,52,53], based on Crow's [54] proposal that the opportunity for selection is proportional to the variance in fitness divided by the square of mean fitness. Many alternative ways of estimating the intensity of sexual selection have been proposed, and the issue remains highly controversial [37,42,48,49,55]; the 'opportunity for sexual selection' can be highly dependent on the details of the biology of a given species [56] and may not be equivalent to its intensity [42]. Following Darwin and Bateman, Trivers [29] proposed relative PI as a measure of the intensity of sexual selection, followed by Emlen & Oring [57] who proposed the operational sex ratio (OSR; the relative number of males and females immediately available to mate in a given locality), followed by Clutton-Brock & Vincent's [58] suggestion of potential reproductive rates (PRR; the potential rate at which a given sex can produce offspring if unlimited by mating with the opposite sex).…”
Section: Bateman's Principlesmentioning
confidence: 99%